2014
DOI: 10.1093/pasj/psu083
|View full text |Cite
|
Sign up to set email alerts
|

Properties of small-scale magnetism of stellar atmospheres

Abstract: The magnetic field outside of sunspots is concentrated in the intergranular space, where it forms a delicate filigree of bright ribbons and dots as seen on broad band images of the Sun. We expect this small-scale magnetic field to exhibit a similar behavior in stellar atmospheres. In order to find out more about it, we perform numerical simulations of the surface layers of stellar atmospheres. Here, we report on preliminary results from simulations in the range between 4000 K and 6500 K effective temperature w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
14
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 14 publications
7
14
1
Order By: Relevance
“…Comparing row 12 with row 1 we readily find that the strength of the magnetic flux concentrations, by far, do not reach thermal equipartition for the K-type atmospheres, but reach close to equipartition for the model F5V. In fact, maximal field strengths can reach superequipartition for models G2V and F5V as already noted by Steiner et al (2014). This is now confirmed in the present work, which shows max(|B z (z 0 )|) in row 3.…”
Section: Characteristics Of the Magnetic Flux Concentrationssupporting
confidence: 88%
See 2 more Smart Citations
“…Comparing row 12 with row 1 we readily find that the strength of the magnetic flux concentrations, by far, do not reach thermal equipartition for the K-type atmospheres, but reach close to equipartition for the model F5V. In fact, maximal field strengths can reach superequipartition for models G2V and F5V as already noted by Steiner et al (2014). This is now confirmed in the present work, which shows max(|B z (z 0 )|) in row 3.…”
Section: Characteristics Of the Magnetic Flux Concentrationssupporting
confidence: 88%
“…Beeck et al (2011) reported on MHD simulations, starting from the same six models mentioned above but introducing initial homogeneous vertical magnetic fields with strengths of 20 G, 100 G, and 500 G. These authors found distinctive differences between solar-like small-scale magnetic structures and those forming in M dwarfs, where the latter are more pore-like. Steiner et al (2014) analyzed MHD models of spectral types K8V to F5V 1 , concluding that the field strength of the strongest flux concentrations (i) was fairly independent of spectral type when measured at the optical depth level τ R = 1; (ii) assumed thermal superequipartition for the Sun and warmer atmosphere, while staying much weaker for cool atmospheres; and (iii) that their presence correlates with enhanced bolometric radiative intensity and flux. Beeck et al (2015a,b) thoroughly analyzed their mainsequence models of spectral types M2V to F3V and of various initial magnetic field strengths and, inter alia, confirmed the findings (i) to (iii), extending their validity to a wider range of spectral types and magnetic fluxes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not a surprising result since the thermal pressure in the photosphere of the simulated white dwarfs is only slightly larger than that in the Sun, and a similar magnetic pressure is necessary to inhibit convective flows. Studies of the impact of magnetic fields on surface convection in the Sun and Sun-like stars by numerous RMHD simulations (Rempel et al 2009;Cheung et al 2010;Freytag et al 2012;Beeck et al 2013;Steiner et al 2014) can also be used to learn about the same process in white dwarfs, even though the origins and large-scale structures of magnetic fields are very different. Figure 2 presents the temperature profiles of our simulations, drawn from the average of T 4 á ñ over surfaces of constant τ R for 12 snapshots.…”
Section: Magnetohydrodynamic Simulationsmentioning
confidence: 99%
“…Until a few years ago, MHD simulations of this kind were only available for the Sun. Recently, the first comprehensive 3D radiative MHD simulations for stars other than the Sun were presented (Beeck et al 2011;Wedemeyer et al 2013;Steiner et al 2013Steiner et al , 2014Beeck et al 2015b). …”
Section: Introductionmentioning
confidence: 99%